Experimental and micromechanical modelling of randomly oriented zalacca fibre/low-density polyethylene composites fabricated by hot-pressing method. Issue 1 (1st January 2018) - Raharjo, Wahyu Purwo; Soenoko, Rudy; Purnowidodo, Anindito; Choiron, Moch Agus
Abstract: This study aims to investigate the effect of the volumefraction of zalacca fibres on the tensile strength and modulus of the LDPE-ZF composites both experimentally and analytically. The tensile tests were carried out on the randomly oriented LDPE-ZF composites manufactured by hot-pressing method. Hirsch and Bowyer–Bader's model was used to predict the tensile strength of the composites where the elastic modulus was determined by using Tsai–Pagano, Manera and Cox–Krenchel's model. The experimental results of tensile strength and elastic modulus of the composites was close by the Bowyer–Bader and Tsai–Pagano's model, respectively. It is due to the consideration of fibre length and orientation factor in the Bowyer–Bader's model and fibre elastic anisotropy in the Tsai–Pagano's model. This study establishes that the hot press method is applicable for processing LDPE-ZF composites